1991
DOI: 10.1172/jci115336
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidic acid as a second messenger in human polymorphonuclear leukocytes. Effects on activation of NADPH oxidase.

Abstract: IntroductionReceptor-mediated agonists, such as FMLP, induce an early, phospholipase D (PLD)-mediated accumulation of phosphatidic acid (PA) which may play a role in the activation of NADPH oxidase in human PMN. We have determined the effect of changes in PA production on 02 consumption in intact PMN and the level of NADPH oxidase activity measured in a cell-free assay. (13, 14) and others (15-18) have demonstrated that FMLP also activates a phospholipase D (PLD) that hydrolyzes choline-containing phosphoglyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
56
0
1

Year Published

1992
1992
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(60 citation statements)
references
References 56 publications
3
56
0
1
Order By: Relevance
“…Taken together, the present results strongly suggest that high glucose level stimulated ROS production through PKC-dependent activation of NAD(P)H oxidase in cultured vascular cells. Although PKC inhibitor normalized the increased ROS production induced by high glucose level statistically completely, it should be stated that phosphatidic acid also can stimulate NADPH oxidase (50,51). Because phosphatidic acid is an intermediate of de novo DAG synthesis, its level should be increased by high glucose level.…”
Section: Resultsmentioning
confidence: 99%
“…Taken together, the present results strongly suggest that high glucose level stimulated ROS production through PKC-dependent activation of NAD(P)H oxidase in cultured vascular cells. Although PKC inhibitor normalized the increased ROS production induced by high glucose level statistically completely, it should be stated that phosphatidic acid also can stimulate NADPH oxidase (50,51). Because phosphatidic acid is an intermediate of de novo DAG synthesis, its level should be increased by high glucose level.…”
Section: Resultsmentioning
confidence: 99%
“…The small molecule inhibitors also protected mice from lipopolysaccharide-mediated endotoxic shock and from lung injury in a model of hemorrhage and resuscitation (36). Others have demonstrated that formyl peptide-stimulated neutrophils can be induced to produce PA by a phospholipase D-dependent mechanism (17). In this setting, the PA activated NADPH oxidase.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Fourcade et al (16) have demonstrated that a secretory phospholipase A 2 acts upon membrane microvesicles shed from activated cells to convert PA to LPA. PA is a key intermediate in membrane phospholipid biosynthesis (10), but it can also serve as a second messenger in activated cells (17). PA can be converted to CDP-diacylglycerol or to diacylglycerol by the action of PA phosphatase or to LPA by the phospholipase A 2 .…”
mentioning
confidence: 99%
“…As RelA/p65 is replaced at the TNF-␣ promoter in tolerant THP-1 cells by dimer exchange with RelB (23), we asked whether SIRT1 interacts with the multicomponent repressor complex proteins RelB and heterochromatin linker histone H1 (8,11,24,25). Our previous work showed that RelB promoter recruitment directs facultative heterochromatin formation by first binding to G9a methyltransferase, which methylates H3K9; other members of chromatin modifiers include histone linker H1, heterochromatin protein 1, and DNA CpG methyltransferases DNMT 3a/3b (11,13,25).…”
Section: Sirt1 Remains Bound To Tnf-␣ Promoter During Endotoxin Tolermentioning
confidence: 99%